2023
DOI: 10.1111/exd.14738
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomic expression in indolent versus transforming oral lichen planus

Abstract: Oral lichen planus (OLP) confers an approximately 1% risk of transformation to oral squamous cell carcinoma (OSCC). Early identification of high‐risk OLP would be very helpful for optimal patient management. We aimed to discover specific tissue‐based protein biomarkers in patients with OLP who developed OSCC compared to those who did not. We used laser capture microdissection– and nanoLC–tandem mass spectrometry to assess protein expression in fixed lesional mucosal specimens in patients with indolent OLP (no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…29 TAP1 was also overexpressed in graft versus host disease. 31 While our previous work on OLP identified overexpressed immune-related proteins such as ITGB2, PTPRC and PTPRCAP that overlapped with ones identified in the present study, 13 a more detailed comparison of VLP and OLP revealed many overexpressed proteins are shared, and these proteins are involved in similar pathways, mostly relating to antigen presentation and integrin signalling.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…29 TAP1 was also overexpressed in graft versus host disease. 31 While our previous work on OLP identified overexpressed immune-related proteins such as ITGB2, PTPRC and PTPRCAP that overlapped with ones identified in the present study, 13 a more detailed comparison of VLP and OLP revealed many overexpressed proteins are shared, and these proteins are involved in similar pathways, mostly relating to antigen presentation and integrin signalling.…”
Section: Discussionsupporting
confidence: 63%
“…12 OLP and NOM samples were also previously published in a study of carcinogenesis in OLP. 13 There were insufficient VLP samples associated with development of vulvar SCC to address the question of malignant transformation for VLP.…”
Section: Patient Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…When potential triggers are excluded, doctors prescribe treatments to manage LP and treat the symptoms. As the etiology for LP is unknown and the disease still has no cure [11, 12], researchers, mainly in biology, medicine, and computational biology domains, have attempted to describe the molecular mechanism of LP and gain biological insights, thereby speeding up the drug discovery process [13].…”
Section: Introductionmentioning
confidence: 99%